(untitled) (Research, Society and Development, 2021)
This study aimed to analyze the water quality of a river in the Eastern Amazon and relate the results obtained with the lack of basic sanitation in the region. Two samples were collected from strategic points of the river and were submitted to the collimetry technique with multiple tubes to calculate the most probable number (MPN) of thermotolerant coliforms present in the water. The samples were then seeded on CLED and Hektoen agar and analyzed in a mass spectrophotometer for final identification of microorganisms. A high number of thermotolerant coliforms was detected, in addition to bacteria of clinical importance, such as Pseudomonas aeruginosa, Shigella spp. and Cronobacter sakazakii. The lack of basic sanitation in the community surrounding the river is the main cause for the significant number of thermotolerant coliforms, demonstrated by the discrepancy in the MPN between samples 1 and 2. The difficulties in guaranteeing basic sanitation in the Amazon are highlighted and the need to implement public policies and carry out health surveillance studies in these populations is reinforced.